Phaseolus vulgaris Seeds from the Late Sixteenth–Early Seventeenth Century AD Ancestral Oneida Diable Site, New York - Hart, John P. (Ethnobiology Letters, 2022)
The ethnohistorical, ethnographic, and contemporary literatures all suggest that common bean (Phaseolus vulgaris) was an important component of Northern Iroquoian agronomic systems and diets. Seemingly at odds with this is the sparse occurrence of whole and partial common bean seeds on fourteenth through seventeenth century AD village sites. The recovery of a large quantity of whole and partial bean seeds from the ancestral Oneida Diable site, dated here to between AD 1583 and 1626 with a Bayesian model using seven new AMS radiocarbon dates, provides clues as to when large quantities of rehydrated/cooked common bean seeds may occur in the archaeological record.